Distinctive clinical features of early and late-onset Ménière’s disease - Lin, Jianwei; Xiao, Heng; Lin, Chenxin; Huang, Gengliang; Guo, Xiaojing; Cai, Huimin; Ye, Shengnan (Frontiers in Neurology, 2025)
PurposeTo compare the clinical characteristics of patients with early and late-onset Ménière’s disease (MD) and to investigate the impact of psychological factors between the two groups.MethodsThe patients were divided into two groups based on their age of onset: early-onset (<45 years old) and late-onset (>55 years old). The differences in clinical symptoms, auditory, vestibular examination, gadolinium-enhanced MRI, vertigo, and psychological assessment were compared. To assess the severity of vertigo, the Dizziness Handicap Inventory (DHI) and Visual Analogue Scale (VAS) were used. The Patient Health Questionnaire 9-item (PHQ-9) and the Generalized Anxiety Disorder 7-item (GAD-7) scales were used to assess the patient’s psychological status.ResultsThirty-five patients were included in the early-onset and thirty-seven in the late-onset MD groups. Tinnitus was more common in the early-onset group. The aggravating (fatigue) and alleviating (ambient quiet; acute rest) factors of a vertigo episode were statistically different between the two groups. The severity of vestibular endolymphatic hydrops, abnormal rate of canal paresis (CP) value of the caloric test, total DHI score, and VAS score were all higher in the late-onset group. PHQ-9 and GAD-7 scores were significantly correlated with total DHI score in the early-onset group.ConclusionEarly-onset patients have a higher incidence of tinnitus and are more prone to experience vertigo bouts brought on by fatigue. In late-onset patients, vestibular endolymphatic hydrops are more severe, and the vertigo symptoms are more pronounced. Psychological factors are more closely related to the symptoms of vertigo in early-onset patients.